The Implementation of Tolerance Values in Grade V Elementary School Students - Ramadani, Nuresi; Pratiwo, Yuda; Hendriana, Evinna Cinda; Mertika, Mertika (Pedagogik Journal of Islamic Elementary School, 2021)
The objectives to be achieved in this study are to determine: a description of the implementation and the supporting and inhibiting factors in the implementation of tolerance values in the fifth-grade students of SDN 7 Singkawang. This type of research is a type of descriptive qualitative research. Data collection techniques were carried out by observation and interviews, while additional data was in the documentation. This study uses data analysis techniques with three paths, namely data reduction, data presentation, and verification. The results of this study indicate that the implementation of tolerance values in fifth-grade students of SDN 7 Singkawang is in the form of being able to respect the opinions of others, being able to accept gracefully if they are wrong, being able to express their opinions politely, and not offending others both in words and actions. Factors that influence the implementation of tolerance values in fifth-grade students at SDN 7 Singkawang are categorized into two factors, namely supporting factors and inhibiting factors. Supporting factors are self-awareness, a sense of nationalism in diversity, parents support, teacher encouragement, and support from schools. The inhibiting factor is a closed personality.